PENGARUH BRAND AMBASSADOR BLACKPINK TERHADAP BRAND IMAGE TOKOPEDIA PERIODE 2021 - Nurazhari, Luthfiah; Putri, Yuliani Rachma (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
This study aims to find out how much Influence BLACKPINK Brand Ambassadors Have on Tokopedia Brand Image for the 2021 Period. Research is based on the phenomenon that occurs where the use of brand ambassadors is not always successful to improve the company's brand image. This happened during the appointment of Shopee BLACKPINK brand ambassador which led to controversy among the public with a petition to stop BLACKPINK advertising on social media because BLACKPINK used clothing and dance that was inappropriate with culture in Indonesia so that KPI gave a reprimand to Shopee to stop BLACKPINK advertising. But when Tokopedia used BLACKPINK as a brand ambassador, it received a positive response from the Indonesian people followed by an increase in the number of tokopedia web monthly visits in January 2021 so that it became the first position e-commerce beat Shopee when using BLACKPINK to become a brand ambassador. The variables used in this study are Brand Ambassador as an independent variable and Brand Image as a dependent variable. This research uses quantitative methods with data analysis techniques using simple linear analysis. This research resulted in an increase in brand ambassadors by one unit, so that the brand image will increase by 0.317 one unit. The influence of BLACKPINK brand ambassadors on brand image was 23.5%, so the remaining 76.5% was influenced by other factors not studied in this study. Keywords : Brand, Brand Ambassador, Brand Image